Bioanalysis by Immobilization of Antibodies on Hafnium(IV) Oxide with 3-Aminopropyltriethoxysilane. (12th December 2017) - Ortiz-Dosal, Luis C.; Kolosovas-Machuca, Eleazar S.; Carmen Rodríguez-Aranda, M.; López-Luna, Edgar; Hernández-Arriaga, Heber; Vera-Reveles, Gustavo; Gonzalez, Francisco J.
ABSTRACT: Self-assembled monolayers of 3-aminopropyltriethoxysilane (APTES) are commonly used to promote adhesion between substrates and organic or metallic materials with applications ranging from advanced composites to biomolecular lab-on-a-chip devices. In this work, the silanization on hafnium oxide (HfO2 ) films is reported. The layers of HfO2 were deposited on Si (001) substrates by atomic layer deposition. The grown HfO2 films were modified in accordance with three main steps: oxidation, silanization, and cross-linking of the APTES monolayer using glutaraldehyde as cross-linking agent. Microscopic features were characterized by atomic force microscopy. Further, both bovine serum albumin and antibovine serum albumin agents were deposited on the samples to test their potential use as the immunosensor.